Molecular modeling of highly selective CDK1 Inhibitors based on pyrazolo-pyrimidines using 3D-QSAR, docking, and molecular dynamics simulations - Muhammad Afaq Tahir; Tahir Ali Chohan; Aisha Qayyum; Abdullah Yahya Abdullah Alzahrani; Abdullah R. Alzahrani; Zia Ur Rehman; Abida Khan; Khuram Ashfaq (PLoS ONE, 2026)
Cyclin-dependent kinase 1 (CDK1) has emerged as a compelling target for anticancer drug development due to its essential role in cell cycle regulation. In this study, a series of pyrazolopyrimidine-based inhibitors was investigated through an integrated computational approach that combined molecular docking, three-dimensional quantitative structure-activity relationship (3D-QSAR) modeling, and molecular dynamics simulations. CoMFA and CoMSIA models were established to elucidate the structural features influencing CDK1 inhibition, demonstrating high reliability with q² and r² values of 0.58 and 0.945, respectively. Docking studies using the crystal structure of CDK1 (PDB ID: 4Y72) revealed key interactions and hotspot residues, such as L83, V18, and D86, which contribute significantly to ligand binding. From a library of 100 in-house compounds, compounds 34 and 37 exhibited strong binding affinities (−12.61 and −12.50 kcal/mol) and were further evaluated through molecular dynamics simulations. The stability of these complexes was supported by RMSD analysis and binding free energy calculations (−94.99 kcal/mol for compound 34). Moreover, ADMET profiling indicated favorable pharmacokinetic properties and synthetic accessibility. These findings offer critical insights into the structural determinants of CDK1 inhibition and support the further development of pyrazolopyrimidine scaffolds as potential anticancer agents.